1996
DOI: 10.1021/jp952167y
|View full text |Cite
|
Sign up to set email alerts
|

Selective Photodissociation of Trapped Ions after Ion Cloud Manipulation with an Impulsive Quadrupolar Electric Field

Abstract: Trapped ions of different masses can be separated in space within a quadrupole ion trap, making it possible to perform efficient mass-selective photodissociation on a mixture of ions. This method employs an axial quadrupolar dc pulse (1 µs) to force all ions into coherent radial motion; ions of the same mass-to-charge ratio are either in phase or phase-shifted by exactly 180°. After this activating pulse, the ions continue to oscillate at their secular frequency in a coherent fashion so that ions of the same m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…The initial distribution widths were equilibrium values obtained from preliminary simulations and are consistent with experimentally determined values, 16,19 if the somewhat different ion mass is taken into account. Subsequently, the ions were subject to ac resonance excitation fields and dc pulses using equivalent parameters to those used in the experiment.…”
Section: Simulationssupporting
confidence: 84%
See 2 more Smart Citations
“…The initial distribution widths were equilibrium values obtained from preliminary simulations and are consistent with experimentally determined values, 16,19 if the somewhat different ion mass is taken into account. Subsequently, the ions were subject to ac resonance excitation fields and dc pulses using equivalent parameters to those used in the experiment.…”
Section: Simulationssupporting
confidence: 84%
“…These slots affect the fields experienced by the trapped ions and, among other consequences, are known to cause mass shifts. 19 As an alternative to the use of laser photodissociation to monitor the position of an ion cloud, Weil et al 21,27 showed that dc tomography could be used to characterize ion motion. In this experiment, the ion population being studied is subjected to a short dipolar or monopolar dc pulse of appropriate amplitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct, high-power, non-specific ablation clearly has drawbacks. Not only can space-charge effects induced by extraneous ions degrade mass accuracy and resolution, 25 but the RF suppression described here can degrade trapping performance. A selective ionization scheme for direct analysis of solid materials, such as resonant laser ablation, seems to be a logical coupling of technologies in that analyte ions are selectively created in the absence of bulk matrix ions, reducing or eliminating space-charge effects.…”
Section: Induced Charge On Ring-electrode Experimentsmentioning
confidence: 99%
“…By adjusting the DC and RF potentials on the linear quadrupole, we can select the ions of a particular mass-to-charge ratio (m/z) prior to their introduction to the ion trap [8]. In this fashion, we can reduce space charge effects, which will lead to improved mass spectral quality in terms of peak shape and mass measurement accuracy, [9] and mass selective storage will provide lower detection limits by allowing the selective accumulation of only those ions of analytical interest [10]. While mass selection of ions can be effected by applying broad-band waveforms to the ion trap to resonantly eject unwanted ions, it is our experience that external mass isolation leads to higher mass spectral quality than allowing all ions to enter the ion trap and then be ejected by resonant excitation methods.…”
Section: Technical Description Of Workmentioning
confidence: 99%